Future perspectives of circulating tumor DNA in colorectal cancer. Issue 5 (May 2017) - Nadal, C; Winder, T; Gerger, A; Tougeron, David
Tumor biopsy is currently the gold standard for diagnosis and in determining cell signaling pathways involved in the development of treatment resistance. However, there are major challenges with this technique, including the need for serial sampling to monitor treatment resistance, which is invasive and also has the potential for selection bias due to intra-tumoral and inter-tumoral heterogeneity. These challenges highlight the need for more effective methods for obtaining Tumor samples. Liquid biopsy analyzes genetic material or tumor cells shed into the blood from the primary tumor and metastatic sites and consequently provides a comprehensive, real-time picture of the tumor burden in an individual patient. Indeed, liquid biopsy has the potential to revolutionize cancer management. Here, we review recent studies on the potential clinical applications of liquid biopsy using circulating tumor DNA in colorectal cancer, including screening, diagnosis, detection of minimal residual disease after surgery, detection of recurrence, prognosis, predicting treatment response, monitoring tumor burden or response during treatment, and tracking resistance. We also discuss recent data demonstrating the utility of detecting KRAS -mutated circulating tumor DNA, both at diagnosis to determine an appropriate treatment strategy and during anti-epidermal growth factor receptor therapy to predict treatment resistance. The future integration of liquid biopsy into clinical practice is discussed, together with alternative approaches and key questions that need to be answered in future clinical studies before this technology can be implemented and used routinely.